Anti-corruption efforts: the importance of the tone at the top - Kleinhempel, Matthias (Organizational corruption, crime and COVID-19, 2025)
The “tone at the top” is a fundamental aspect of any organization’s ethics and compliance program. It is closely intertwined with various elements of an ethics and compliance program, including the corporate governance system, the relationship between the Board of Directors and the Ethics and Compliance Department, the company’s culture, its evaluation and incentive systems, as well as the effectiveness of risk mapping for ethics and compliance risks and integrity in decision-making processes. As a result, ethical and compliant practices must begin with the highest levels of leadership, the “top” of the organization. Without the commitment of the Board and senior management, these efforts are futile. This serves as an important lesson for every ethics and compliance officer.